Building Urban Resilience : Principles, Tools, and Practice - Jha, Abhas K.; Miner, Todd W.; Stanton-Geddes, Zuzana (Washington, DC: World Bank, 2013)
Building Urban Resilience in East Asia is a World Bank program that aims to increase the resilience of cities to disasters and the impacts of climate change by using a risk-based approach to making public investment decisions. The objective is to demonstrate a scalable methodology and practical tools for risk assessment that can be used for city-level investment decisions. Working closely with the stakeholders involved in land use planning and infrastructure development, phase one of this program identified the major challenges facing urban decision makers in terms of risks from natural disasters and climate change and now offers open-source risk assessment tools that can be used by city-level institutions, other communities, private investors, and planners of infrastructure services. Phase two explores different investment options, management plans, and capacity building needs. The goal is to formulate a strategy in which flexible and 'low-regret' measures can be cost-effective even when risks are uncertain. Taking into account future risks and uncertainties, resilience relies on redundancy. Cities facing difficult decisions about scarce resources and investments strive for efficiency. Financial approaches to urban disaster resilience should reduce the negative impacts of disasters on individuals and communities, the private sector, and public entities.